2020
DOI: 10.3390/ph13090254
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate-Loaded Gold Nanoparticles: Preparation and Evaluation of Anticancer Efficacy in Ehrlich Tumor-Bearing Mice

Abstract: Epigallocatechin-3-gallate (EGCG) is a pleiotropic compound with anticancer, anti-inflammatory, and antioxidant properties. To enhance EGCG anticancer efficacy, it was loaded onto gold nanoparticles (GNPs). EGCG-GNPs were prepared by a simple green synthesis method and were evaluated using different techniques. Hemocompatibility with human blood and in vivo anticancer efficacy in Ehrlich ascites carcinoma-bearing mice were evaluated. EGCG/gold chloride molar ratio had a marked effect on the formation and prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Besides, Li et al [ 27 ] reported that the in vitro release of EGCG-loaded niosomal formulations was more sustained than the free drug. Additionally, Safwat et al [ 42 ] demonstrated that free EGCG diffused rapidly throughout the dialysis membrane. By contrast, EGCG-loaded gold nanoparticles exhibited sustained drug release for a prolonged period of time.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, Li et al [ 27 ] reported that the in vitro release of EGCG-loaded niosomal formulations was more sustained than the free drug. Additionally, Safwat et al [ 42 ] demonstrated that free EGCG diffused rapidly throughout the dialysis membrane. By contrast, EGCG-loaded gold nanoparticles exhibited sustained drug release for a prolonged period of time.…”
Section: Resultsmentioning
confidence: 99%
“…As potential drug carriers, AuNPs have received considerable attention by many researchers [ 6 , 7 , 8 , 9 , 10 ], as it has been frequently reported that they can induce programmed cell death (i.e., apoptosis) [ 11 , 12 ]. Furthermore, as drug carriers, AuNPs can transport imaging and therapeutic agents, providing the possibility of diagnosis, treatment, and monitoring therapeutic progress, while AuNPs themselves do not participate in diagnosis or therapy [ 13 , 14 , 15 , 16 , 17 ]. However, AuNPs are rarely reported as agents that can inhibit cell proliferation and achieve both fluorescence-enhanced cell imaging and specific cell targeting.…”
Section: Introductionmentioning
confidence: 99%
“…EGCG has shown beneficial effects on diabetes, cardiovascular diseases, Parkinson’s disease, Alzheimer’s disease, stroke and obesity [ 12 , 16 ]. EGCG possesses anti-mutagenic and anti-carcinogenic effects of environmental agents that increase the risk of cancer development [ 17 , 18 ]. Green tea extract containing EGCG inhibited carcinogenesis in different animal models with lung, skin, esophagus and liver cancers [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%